2021
DOI: 10.1002/aenm.202003829
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Surface Passivation Enables Thermally Stable and Efficient Planar Perovskite Solar Cells Using a Novel IDTT‐Based Small Molecule Additive

Abstract: Although perovskite solar cells (PSCs) have attracted enormous attention owing to their fascinating optoelectronic properties and solution processability, defects in PSCs, which adversely affect efficiency and stability, are still not completely resolved. Herein, a novel indacenodithieno[3,2‐b]thiophene‐based small molecule (SM) additive (IDTT‐ThCz), capable of interacting with perovskite layers, is developed. In particular, the IDTT‐ThCz, which can perform a surface passivation, is introduced into the perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 61 publications
1
89
0
Order By: Relevance
“…Recently, common surface passivators including Lewis bases/acids, organic halide salts, polymers, fullerenes, and their derivatives have been used to passivate the defects of perovskite film [ 11 15 ]. Among them, most Lewis bases/acids, organic halide salts and polymers possess insulating properties and could hinder efficient carrier extraction at the interface owing to their poor conductivity, and negatively affect the reproducibility of PSCs due to a distribution in molecular weights [ 16 ]. The fullerenes and their derivatives such as PCBM require many steps for synthesis, are expensive, and exhibit low yields [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, common surface passivators including Lewis bases/acids, organic halide salts, polymers, fullerenes, and their derivatives have been used to passivate the defects of perovskite film [ 11 15 ]. Among them, most Lewis bases/acids, organic halide salts and polymers possess insulating properties and could hinder efficient carrier extraction at the interface owing to their poor conductivity, and negatively affect the reproducibility of PSCs due to a distribution in molecular weights [ 16 ]. The fullerenes and their derivatives such as PCBM require many steps for synthesis, are expensive, and exhibit low yields [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lewis bases/acids, organic halide salts and polymers possess insulating properties and could hinder efficient carrier extraction at the interface owing to their poor conductivity, and negatively affect the reproducibility of PSCs due to a distribution in molecular weights [16]. The fullerenes and their derivatives such as PCBM require many steps for synthesis, are expensive, and exhibit low yields [17,18].…”
mentioning
confidence: 99%
“…Meanwhile, indaceno [1,2-b : 5,6-b']dithiophene (IDT)-based polymers have planar and rigid structures, which enable strong intermolecular interactions between polymer chains. [105] IDT-based polymers retain their morphology at high temperatures [106] and are strong candidates for polymer additives. Yang et al employed an IDTbased polymer (1 wt % PZ1) in the PM6 : BTTT-2Cl blend and observed the suppressed crystallization of BTTT-2Cl by GIWAXS analysis (i. e., no crystallite peak in BTTT-2Cl film treated for 24 h at 150°C).…”
Section: Morphology Fixation For Device Stabilitymentioning
confidence: 99%
“…21,35 Therefore, much effort has been devoted to developing interfacial materials with semiconducting properties that can simultaneously passivate defects and improve interfacial hole extraction. [36][37][38][39] For instance, Li et al reported a pyrene based two-dimensional molecule SMe-TATPyr incorporating thiophene and methylthio functionalized triphenylamine as a bifunctional interfacial material to address the above mentioned issues, achieving a PCE of 22.3%. 40 Recently, a dithienopyrrolobenzothiadiazole (DTPBT) based hole transporting interfacial layer was employed by Wang et al to passivate defects via Pb-N/S interactions and slow down the generation of the d phase.…”
Section: Introductionmentioning
confidence: 99%